Attitudes and perceptions of first year students towards interprofessional education in the Faculty of Community and Health Sciences at the University of the Western Cape - Filies, Gerard C. (Stellenbosch : Stellenbosch University, 2013)
ENGLISH ABSTRACT: The setting for this study was the University of the Western Cape, Faculty of Community and Health Sciences, first year undergraduate students. All students who participated in the compulsory interprofessional programme were from the following disciplines: Occupational Therapy; Physiotherapy; Psychology; Social Work; Natural Medicine; Dietetics; Human Ecology; Sports Sciences and Nursing. The objectives of this study were to measure the attitudes and perceptions of first year students who participated in an undergraduate interprofessional programme. The attitudes and perceptions were further measured in relation to the specific lecturers involved, the age of the students, their gender, race, background as well their specific discipline. This was primarily a quantitative study incorporating two qualitative questions in which 657 students were issued with a questionnaire designed to determine their attitudes and perceptions towards interprofessional education. A sample size of 264 students resulted in 95% confidence intervals with a maximum precision of 5%. The questionnaire was adapted, with permission, from Cameron; Rennie; DiProspero; Langlois & Wagner (2009). MS Excel was used to capture the data and STATISTICA version 9 (StatSoft Inc. (2009) STATISTICA (data analysis software system), www.statsoft.com.) was used to analyze the data from the questionnaires. Descriptive statistics was used to describe the main features of the sample of this study and summary statistics was further used to summarize the findings of this study in order to communicate the bulk of the information as simple as possible. Two open-ended questions were included at the end of the questionnaire and this was used to triangulate the data. The Kruskal-Wallace test was used to measure the results, whereby a p-value of <0.05 indicated statistical significance. Of all the factors used to measure the attitudes and perceptions of students, the following three were significant: Gender; Race and Discipline. No other factors impact on the attitudes and perceptions of students towards interprofessional education. Student attitudes and perceptions towards interprofessional education were found to be very positive. The findings revealed that the most significant factor in the study was the lack of understanding of various disciplines participating in the programme and their understanding of the relevance of the teaching approach (interprofessional) as well as their specific role in the health care team. This clearly illustrated the need to recommend to the co-ordinating unit of the programme that this be defined more clearly for the students and specifically the Sports Sciences students.